CHARACTERIZATION OF POROPERM DEVELOPMENT IN APALEOZOIC CARBONATE RESERVOIR ANALOG, NORTHERN VIETNAM - Hoang Nguyen, Anh (Bulletin of Earth Sciences of Thailand, 2021)
In offshore northern Vietnam, a number of vertical wells have been drilled to test “buried-hill” plays in fractured Devonian carbonates, sealed by shale. So far, there has been little success, with either dry holes, or wells showing low subeconomic rates of return when tested. So the question that needs to be answered for this play type is: why did they fail and how can we target more successfully in this play type? A detailed geological characterization of fractured Devonian carbonates was undertaken in a quarry outcrop (20058’40’’N latitude and 106041’43’’E longitude) in the Thuy Nguyen district of Northern Vietnam. This work integrates the results of detailed mapping and interpretation of lithologies and fracture orientations, along with detailed petrographic and isotopic analyses and leads to the following conclusions. (1) Significant levels of poroperm in fractured Devonian carbonates in the region are mostly confined to NE-SW fracture sets created and enlarged in the telogenetic realm; fracture trend relates to uplift in a stress field created by movement of the Red River Fault. (2) Equivalents to this style of diagenesis likely occur in subsurface as potential fractured Devo-nian reservoirs in the nearby offshore. (3) Successfully exploring and developing such reservoirs will require directional (not vertical) wells and a better rock-based understanding of the controls, orientations, timings of major fracture events (requires outcrop and core-calibrated FMI interpretation). (4) Poroperm predictions in subsurface counterparts require an improved understanding of fluid evolution and the relative timing of the various diagenetic events that can occlude or enhance porosity and permeability in both matrix and fractures (requires detailed petrographic study tied to texture-aware isotope sampling of cuttings or core).